The impact of COVID-19 on cultural industries: An empirical research based on stock market returns - Zhang, Rong; Ji, Hao; Pang, Yu; Suo, Lingling (Frontiers in Public Health, 2022)
The emergence of COVID-19 has challenged the development of the cultural industry seriously. In order to explore the impact of the epidemic on the development of the cultural industry, this paper used a fixed-effect model to analyze the impact of COVID-19 on the stock market returns of cultural industry, based on the panel data of listed companies from Chinese cultural industry. The empirical results show the following results. Firstly, the stock market return of the cultural industry is negatively correlated with the severity of COVID-19. Secondly, there are significant differences in the impact of the epidemic on different types of cultural industries. Thirdly, digitization can significantly reduce the negative impact of COVID-19 on the cultural industry. We also found that the negative impact of the epidemic on small-scale and young cultural enterprises is more serious. Moreover, the empirical research shows that the impact of COVID-19 on the stock market returns of the cultural industry has a tendency to first increase and then gradually decrease. Based on these conclusions, we finally put forward relevant government policies and countermeasures for cultural enterprises.